Psychological Distress Among Cancer Patients During COVID-19 Pandemic in the World: A Systematic Review - Momenimovahed, Zohre; Salehiniya, Hamid; Hadavandsiri, Fatemeh; Allahqoli, Leila; Günther, Veronika; Alkatout, Ibrahim (Frontiers in Psychology, 2021)
Aim: patients with malignancies, experience high rates of psychological distress. Fear of infection combined with the interruptions in some treatment programs affect mental health of cancer patients. Reducing the mental suffering of cancer patients requires accurate knowledge of the effects of pandemics on the incidence of mental disorders, so this review study was conducted to investigate the psychological distress among cancer patients during covid pandemic. Materials and methods: To identify the psychological distress of cancer patients, a comprehensive search was carried out in databases such as; PubMed, Web of Science Core Collection, and Scopus using keywords including mental health, distress, anxiety, depression, psychiatric disorder, cancer, tumor, oncology, malignancy, and neoplasms. Full-texted, English language and original articles were included in this study. Results: In total, 18 articles were entered into the study. The findings of this study revealed Covid-19 greatly affects mental health of cancer patients. These patients experience a significant psychological burden at the covid time. Depression, isolation, anxiety, insomnia and fear are the most important psychological problems of cancer patients during the covid-19 pandemic. Conclusion: The covid-19 related anxiety is an expected reaction to the current situation. Although psychological distress affects many people, it can confuse cancer patients to the point that they refuse to continue treatment for the fear of infection and worsening of their condition. Since the end of this pandemic is unknown, this action can endanger the health of this group of patients, so it seems that using psychological interventions in the current situation is one of the main priorities for cancer patients.